Evaluation of the 3M™ Molecular Detection Assay (MDA) 2 – Cronobacter for the Detection of Cronobacter species in Select Foods and Environmental Surfaces: Collaborative Study, First Action 2018.01. (23rd November 2019) - Bird, Patrick; Benzinger, M Joseph; Bastin, Ben; Crowley, Erin; Agin, James; Goins, David; Monteroso, Lisa; ,
Abstract: The 3M™ Molecular Detection Assay (MDA) 2 – Cronobacter combines the use of loop-mediated isothermal amplification to rapidly amplify nucleic acid sequences while using bioluminescence to detect the amplification. Using a paired study design, the MDA 2 – Cronobacter was compared with ISO 22964:2017 for the detection of Cronobacter species in powdered infant formula containing probiotics. Technicians from 11 laboratories from the United States, Mexico, and Croatia participated. Collaborators received test portions with three levels of contamination. Statistical analysis was conducted according to the probability of detection (POD) statistical model. Results obtained for the low-inoculum level test portions produced a difference in POD values obtained from combining all valid collaborator POD data values with 95% confidence intervals of –0.01, –0.12, and 0.10, indicating that the difference between methods was not statistically significant at the 0.05 probability level.